Los elementos esenciales del contrato de trabajo - Pacheco Zerga, Luz (Revista de Derecho, 2019)
The author examines the essential elements of the employment contract containedin the Labour Productivity and Competitiveness Law and its treatment by nationaljurisprudence and comparative law in order to identify the service relationships thatcorrespond to the employment contract and grant social protection they deserve.
Keywords: contract of employment; personal services; salary; subordination; power steering; power disciplinary; work schedule